A cross-linguistic investigation of Malay and English temporal systems - Lotfie, Maskanah Mohammad (2010)
This cross-linguistic study traces the patterns of Malay and English linguistic subsystems and investigates similarities and differences between them. It focuses on the lexico-grammatical features of the two languages and in particular, on present time temporal references. The data collection of this study involved the production of Malay and English written corpora from two groups of Malay native speakers who used English as a second language at the tertiary level. Detailed analysis of the written output provides an elucidation of tranfer issues and clarifications of first language-second language (L1-L2) relationships in the acquisiton of temporal systems. Acquisitional patterns of target items have been traced where the patterns substantiate the differences between Malay and English present time forms with acquisitional difficulties being observed in the features that are incompatible in the two languages.